Development of Next Generation Vaccines against SARS-CoV-2 and Variants of Concern - Abdul Aziz, Al-Fattah Yahaya *; Kanwal, Khalid *; Lim, Hui Xuan *; Poh, Chit Laa * (MDPI, 2023)
SARS-CoV-2 has caused the COVID-19 pandemic, with over 673 million infections and 6.85 million deaths globally. Novel mRNA and viral-vectored vaccines were developed and licensed for global immunizations under emergency approval. They have demonstrated good safety and high protective efficacy against the SARS-CoV-2 Wuhan strain. However, the emergence of highly infectious and transmissible variants of concern (VOCs) such as Omicron was associated with considerable reductions in the protective efficacy of the current vaccines. The development of nextgeneration vaccines that could confer broad protection against both the SARS-CoV-2 Wuhan strain and VOCs is urgently needed. A bivalent mRNA vaccine encoding the Spike proteins of both the SARS-CoV-2 Wuhan strain and the Omicron variant has been constructed and approved by the US FDA. However, mRNA vaccines are associated with instability and require an extremely low temperature (−80 ◦C) for storage and transportation. They also require complex synthesis and multiple chromatographic purifications. Peptide-based next-generation vaccines could be developed by relying on in silico predictions to identify peptides specifying highly conserved B, CD4+ and CD8+ T cell epitopes to elicit broad and long-lasting immune protection. These epitopes were validated in animal models and in early phase clinical trials to demonstrate immunogenicity and safety. Nextgeneration peptide vaccine formulations could be developed to incorporate only naked peptides, but they are costly to synthesize and production would generate extensive chemical waste. Continual production of recombinant peptides specifying immunogenic B and T cell epitopes could be achieved in hosts such as E. coli or yeast. However, recombinant protein/peptide vaccines require purification before administration. The DNA vaccine might serve as the most effective next-generation vaccine for low-income countries, since it does not require an extremely low temperature for storage or need extensive chromatographic purification. The construction of recombinant plasmids carrying genes specifying highly conserved B and T cell epitopes meant that vaccine candidates representing highly conserved antigenic regions could be rapidly developed. Poor immunogenicity of DNA vaccines could be overcome by the incorporation of chemical or molecular adjuvants and the development of nanoparticles for effective delivery